Executing Quality Management Tools to Enhance Customer’s Journey at a Clothes Laundry Firm - Alshahrani, Mohammed; Alabdali, Mahmoud; Zaid, Wafa; Mohammed, Rola; Husain, Khalid S. M. (European Scientific Journal, ESJ, 2022)
Purpose: This project aims to assess and enhance the customer’s journey at a laundry company in Saudi Arabia from when the customer arrives at the parking lot of the laundry store until receiving the services and payment. Design, methodology, approach: A mixed-method approach was employed, in which qualitative data were gathered from focus group interviews and solo interviews, and quantitative data were gathered through the survey. Moreover, Quality Management Tools were used to build the action plan and offer conclusions and recommendations that would enhance the customer’s journey and improve satisfaction. Findings: Services quality issues are categorized into five categories: promotions, human resources; services; detergent products, and facilities. House of Quality represents the highest 15 prioritized solutions. These recommended solutions’ relative weights range between 9% to 4%. The use of these tools highlights areas for improvement and the root causes of each issue. The seven quality tools are trustworthy tools to conquer challenges faced by the company and may be effective in improving service quality to positively strengthen organizational performance, customer satisfaction, and success. Originality, value: There are limited studies practically employing the seven Quality Management Tools to enhance customer satisfaction and improve their journey. The Saudi laundry market specifically has a dearth of this type of study. Furthermore, this market has seen rapid growth since it is known as a part of the SME sector in recent few years.